Analisis Rasio Profitabilitas dan Solvabilitas Untuk Menilai Kinerja Keuangan: Studi Empiris Perusahaan Industri Barang Konsumsi Sub Sektor Farmasi yang terdaftar di BEI Tahun 2015-2020 - Gumelar, Gugun; Evianti, Dessy (Institut Bisnis dan Informatika Kesatuan, 2022)
Financial Performance is the result or achievement that has been achieved by the company's management in carrying out its function in managing company assets effectively for a certain period. This financial performance is needed by the company to know and evaluate the extent of the company's success rate based on the financial activities that have been carried out. Stock returns can be used as a performance measure, because stock returns can interpret the company's management ability in carrying out its business to get results from good financial performance. Therefore, it is necessary to measure Profitability ratios (Return on Assets, Return on Equity, Net Profit Margin) and Solvency ratios (Debt to Asset Ratio, Debt to Equity Ratio). This study aims to determine the effect of Profitability Ratios (Return on Assets, Return on Equity, Net Profit Margin) and Solvency Ratios (Debt to Asset Ratio, Debt to Equity Ratio) on the financial performance of a company. The sample used is the financial statements of the Indonesia Stock Exchange with the Pharmaceutical sub-sector with 05 samples that meet the criteria for research. The research method uses multiple linear regression analysis with simultaneous T test and F test hypothesis testing. The results based on the Partial T Test (1) Return on Assets (ROA) has a negative effect on financial performance, (2) Return on Equity (ROE) has a positive effect on financial performance, (3) Net Profit Margin (NPM) has a negative effect on financial performance. (4) Debt to Asset Ratio has a negative effect on Financial Performance, (5) Debt to Equity Ratio has a positive effect on Financial Performance and for the simultaneous F test, the results show that simultaneously Return on Assets, Return on Equity, Net Profit Margin, Debt to Assets Ratio, Debt to Equity Ratio affect Financial Performance. Keywords: Profitability Ratio, Return on Assets, Return on Equity, Net Profit Margin, Solvency Ratio, Debt to Asset Ratio, Debt to Equity Ratio, Financial Performance, Stock Return.